1977
DOI: 10.1902/jop.1977.48.8.460
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Filament Diameter when Using Bass Brushing Technique

Abstract: A comparative study using a crossover experimental construction was made of the effectiveness of brushes containing 6/10 nylon filaments of 0.132 mm mean diameter using a Bass technique with those containing filaments of the same type of nylon but 0.280 mm diameter. Each type of brush was used for a 2-week period. Even though the finer filament brushes contained more than three times as many filaments, they were inferior in cleaning achievement to the brushes with the broader filaments. The difference was part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Gibson and Wade (7) compared a toothbrush with 0.2 mm diameter filaments and another with 0.18 mm diameter filaments observed a trend that the 0.2 mm filaments cleaned the marginal gingiva more effectively. In a crossover study, Vowles and Wade (30) tested the differences between 0.13 and 0.28 mm filament diameter and found that plaque removal was significant better ( P < 0.001) with the thicker 0.28 mm filaments were used with the roll technique for brushing on the facial and interproximal areas. It appears therefore that filaments must have a degree of stiffness to create sufficient abrasion to dislodge plaque deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Gibson and Wade (7) compared a toothbrush with 0.2 mm diameter filaments and another with 0.18 mm diameter filaments observed a trend that the 0.2 mm filaments cleaned the marginal gingiva more effectively. In a crossover study, Vowles and Wade (30) tested the differences between 0.13 and 0.28 mm filament diameter and found that plaque removal was significant better ( P < 0.001) with the thicker 0.28 mm filaments were used with the roll technique for brushing on the facial and interproximal areas. It appears therefore that filaments must have a degree of stiffness to create sufficient abrasion to dislodge plaque deposits.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, only a low correlation between applied pressure and brushing effectiveness (187, 188). Several studies evaluated the influence of specific features, such as bristle design (8, 20, 23, 26, 39, 63, 148, 191), toothbrush head (165, 181, 202, 212) and handle (51, 96, 97, 104) on the efficacy of a toothbrush. Although minor differences in the effectiveness of various toothbrushes were found, the clinical relevance of these findings is unclear.…”
Section: Patient‐performed Plaque Controlmentioning
confidence: 99%
“…7,22 The modified Bass technique was chosen for this study as the soft texture bristle tips removed plaque from the cervical area of teeth along the free gingival margin and facilitated intra-sulcular brushing without causing abrasive trauma to the gingiva. 15,16,27 In this study none of the participants reported of any incident of gingival abrasion during the entire course of the study while using either of T1 or T2. Literature does suggest that 0.2 mm bristle filaments effectively removed plaque better as compared to narrower diameter bristle filaments while brushing with the Bass technique.…”
Section: Discussionmentioning
confidence: 63%
“…Literature does suggest that 0.2 mm bristle filaments effectively removed plaque better as compared to narrower diameter bristle filaments while brushing with the Bass technique. 9,16,27 Both T1 and T2 had the same bristle tip diameter of 0.01 mm; therefore, their comparison with bristle diameter of 0.2 mm was beyond the scope of this study. In this study, the inter-group difference in WI at baseline was not statistically significant (p = 0.084) indicating that the new toothbrushes T1 and T2 bristles displayed no wear during dispensing at the start of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation